2016
DOI: 10.1074/jbc.m115.686253
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Neo1 Protein from Budding Yeast Plays a Role in Establishing Aminophospholipid Asymmetry of the Plasma Membrane

Abstract: Eukaryotic organisms typically express multiple type IV P-type ATPases (P4-ATPases), which establish plasma membrane asymmetry by flipping specific phospholipids from the exofacial to the cytosolic leaflet. Saccharomyces cerevisiae, for example, expresses five P4-ATPases, including Neo1, Drs2, Dnf1, Dnf2, and Dnf3. Neo1 is thought to be a phospholipid flippase, although there is currently no experimental evidence that Neo1 catalyzes this activity or helps establish membrane asymmetry. Here, we use temperature-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 64 publications
3
57
0
Order By: Relevance
“…Neither ATP9A, TAT5 or Neo1p have biochemically been shown to possess flippase activity. However, strong genetic evidence in C. elegans is consistent with TAT5 regulating the asymmetry of phosphatidylethanolamine 61 and, in budding yeast, inactivation of Neo1p leads to preferential exposure of phosphatidylethanolamine on the outer leaflet 53 , again consistent with a role in phospholipid translocation. In the related yeast flippase Drs2p, a Drs2p(E342Q) mutation blocks the ATPase cycle at the E 2 P conformation, and hence inhibits phospholipid translocation across the bilayer 62 , 63 .…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Neither ATP9A, TAT5 or Neo1p have biochemically been shown to possess flippase activity. However, strong genetic evidence in C. elegans is consistent with TAT5 regulating the asymmetry of phosphatidylethanolamine 61 and, in budding yeast, inactivation of Neo1p leads to preferential exposure of phosphatidylethanolamine on the outer leaflet 53 , again consistent with a role in phospholipid translocation. In the related yeast flippase Drs2p, a Drs2p(E342Q) mutation blocks the ATPase cycle at the E 2 P conformation, and hence inhibits phospholipid translocation across the bilayer 62 , 63 .…”
Section: Resultsmentioning
confidence: 79%
“…Importantly, while attempts at reconstituting the in vitro phospholipid translocation activity of neo1p have so far not been successful because of technical reasons 53 , we have shown that the in vivo ATPase activity of TAT5 is required for the MON2-PAD1-TAT5 dependent SNX3-retromer mediated sorting of Wls. When taken with the published role that the disruption of neo1p, TAT5 and ATP9A all lead to phenotypes consistent with their role in the flipping of phospholipids 53 , 54 , 60 , 61 , 64 , 65 , our data argue that the phospholipid translocation activity of these P4-ATPases is an important component in the endosomal sorting of Wls. Furthermore, in yeast, Snx3p recruits Neo1p to mediate recycling of the known yeast Snx3p-cargo A-ALP, fully supports a role for ATP9A in human SNX3-retromer mediated sorting 65 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…With regard to substrate specificity, the P4-ATPases can be roughly divided into three categories: enzymes that preferentially flip PS and to a lesser extent PE (ATP8A1, ATP8A2, ATP11A, ATP11C, Drs2) (Natarajan et al , 2004, Paterson et al , 2006, Coleman et al , 2009, Yabas et al , 2011, Takatsu et al , 2014), enzymes that preferentially flip PC and PE (ATP8B1, ATP8B2, ATP10A, Dnf1,2, and 3) (Pomorski et al , 2003, Alder-Baerens et al , 2006, Takatsu et al , 2014, Naito et al , 2015), and enzymes whose substrate preference is unknown (ATP9A, ATP9B and Neo1). Although PL translocase activity has not been directly observed for the orthologous ATP9/Neo1 group, it was recently shown that genetic manipulations of Neo1 were capable of altering plasma membrane PE and PS asymmetry, and these observations are consistent with a putative Golgi-resident flippase activity (Takar et al , 2016). In addition, loss of an ATP9 ortholog in C. elegans ( TAT-5 ) also causes a loss of membrane PE asymmetry, suggesting this group may be PE/PS flippases (Wehman et al , 2011).…”
Section: P4-atpase Domain Organization and Catalytic Cyclementioning
confidence: 98%
“…Unfortunately, flippase activities of other P4-ATPases that mainly localize to intracellular compartments, such as ATP9A, ATP9B, ATP10B, and ATP11B, have not been detected by using a cell-based flippase assay (50). Although the phospholipid translocase activity of ATP9/Neo1p has not been directly observed, genetic manipulations of NEO1 alter the asymmetric distributions of PE and PS in the plasma membrane (82). In addition, loss of an ATP9 ortholog (TAT-5) in C. elegans abrogates the membrane asymmetry of PE, suggesting that ATP9/Neo1p might be PE/PS flippases (20).…”
Section: Lipid Transport By P4-atpasesmentioning
confidence: 99%